Human Acellular Amniotic Membrane as Skin Substitute and Biological Scaffold: A Review of Its Preparation, Preclinical Research, and Clinical Application - Yanqi Li; Siyu An; Chengliang Deng; Shune Xiao (MDPI AG, 2023)
Human acellular amniotic membrane (HAAM) has emerged as a promising tool in the field of regenerative medicine, particularly for wound healing and tissue regeneration. HAAM provides a natural biological scaffold with low immunogenicity and good anti-infective and anti-scarring results. Despite its potential, the clinic application of HAAM faces challenges, particularly with respect to the preparation methods and its low mechanical strength. This review provides a comprehensive overview of HAAM, covering its preparation, sterilization, preclinical research, and clinical applications. This review also discusses promising decellularization and sterilization methods, such as Supercritical Carbon Dioxide (SC-CO2), and the need for further research into the regenerative mechanisms of HAAM. In addition, we discuss the potential of HAAM as a skin dressing and cell delivery system in preclinical research and clinical applications. Both the safety and effectiveness of HAAM have been validated by extensive research, which provides a robust foundation for its clinical application.